Rap2a Is Negatively Regulated by NF-κB and Contributes to Growth via Wnt Pathway in Shrimp - Wang, Sheng; He, Mingyu; Li, Qinyao; Li, Haoyang; Yin, Bin; He, Jianguo; Li, Chaozheng (Frontiers in Marine Science, 2022)
Rap2a, a member of Ras family small GTPases, plays a key role in growth and development. So far, no Rap2a homolog has been discovered in crustaceans. Herein, a Rap2a homolog from shrimp Litopenaeus vannamei, named LvRap2a, was cloned and identified. LvRap2a showed a high level of sequence conservation to other Rap2a homologs from different species. LvRap2a was found to be abundantly expressed in hemocytes, muscle, hepatopancreas and intestine tissues. Importantly, Rap2a knockdown effectively suppressed the length and weight of shrimp in a growth experiment. Mechanistically, we found that Rap2a could induce the expression of several Wnts, which are the positive regulators in cellular growth, differentiation, and tissue homeostasis. Moreover, LvRap2a expression was observed to be negatively regulated by LvDorsal (NF-κB), a transcription factor of innate immune signaling pathway. These results indicated that LvRap2a contributed to shrimp growth probably by activating the Wnt signaling pathway, and that LvRap2a could be the crosstalk between innate immunity and growth, as well as that LvRap2a could serve as a potential target for shrimp growth promotion.